PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN LEMBAGA KESEJAHTERAAN SOSIAL ANAK YAYASAN HAMBA - Fr. Reni Retno Anggraini; Ilsa Haruti Suryandari; Firma Sulistiyowati (Universitas Sanata Dharma, 2021)
This community service activity aims to assist The Child Welfare Institution (LKSA) of the HAMBA Foundation in preparing financial statements. Based on the initial observations, this foundation has not prepared financial statements in accordance to Indonesian Accounting Standards about the presentation of non-profit financial statements. This foundation is supposed to present financial statement in accordance to accounting standard for non-profit organization. The activity of this community service begins with (1) identifying and understanding the existing business processes of The Child Welfare Institution of the HAMBA Foundation, (2) accounting principles and practices at The Child Welfare Institution of the HAMBA Foundation, (3) evaluating whether the financial statements that have been prepared are in accordance with the Accounting Standard for Financial statements in Indonesia, and (4) recommendations for improvement to improve the quality of financial statements. The results achieved from this community service are excel software for The Child Welfare Institution of the HAMBA Foundation. Thus, the foundation can make financial statements quickly and accountably. The recommendation for The Child Welfare Institution of the HAMBA Foundation is to continue using the software to compile the financial reports.